2012
DOI: 10.1002/hlca.201200403
|View full text |Cite
|
Sign up to set email alerts
|

Helical Structures of Bicyclic α‐Amino Acid Homochiral Oligomers with the Stereogenic Centers at the Side‐Chain Fused‐Ring Junctions

Abstract: Chiral bicyclic α‐amino acid (R,R)‐Ab5,6=c with stereogenic centers at the γ‐position of fused‐ring junctions, and its enantiomer (S,S)‐Ab5,6=c, were synthesized. The CD spectra of (R,R)‐Ab5,6=c oligomers indicated that the (R,R)‐Ab5,6=c hexapeptide formed a mixture of right‐handed (P)‐ and left‐handed (M)‐310‐helices, while, in the (R,R)‐Ab5,6=c nonapeptide, a right‐handed (P)‐310‐helix slightly dominated over the (M)‐helix. X‐Ray crystallographic analyses of (S,S)‐tripeptide and (R,R)‐hexapeptide revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…The left-handedness of the helix was exclusively controlled by the chiral centers at the side-chain β-carbons of cyclopropane. These results are in contrast to those of the uncontrolled helical screw direction of ( R , R )-Ac 4 c 3BD , ( R , R )-Ab 5,6= c, and ( R , R )-Ac 6 c 35 dBu homopeptides but are in accordance with the one-handed helical screw of ( S , S )-Ac 5 c dOM homopeptides …”
contrasting
confidence: 77%
See 1 more Smart Citation
“…The left-handedness of the helix was exclusively controlled by the chiral centers at the side-chain β-carbons of cyclopropane. These results are in contrast to those of the uncontrolled helical screw direction of ( R , R )-Ac 4 c 3BD , ( R , R )-Ab 5,6= c, and ( R , R )-Ac 6 c 35 dBu homopeptides but are in accordance with the one-handed helical screw of ( S , S )-Ac 5 c dOM homopeptides …”
contrasting
confidence: 77%
“…Homopeptides composed of a chiral five-membered ring dAA ( S , S )-Ac 5 c dOM with two side chain chiral centers preferentially formed left-handed ( M ) helical structures without an α-chiral center . Contrary to the one-handed helical structure of ( S , S )-Ac 5 c dOM homopeptides, the homopeptides composed of a five,six-membered bicyclic ring dAA ( R , R )-Ab 5,6= c with two side-chain chiral centers, a four-membered ring dAA ( R , R )-Ac 4 c 3BD with a chiral acetal moiety, or a six-membered ring dAA ( R , R )-Ac 6 c 35dBu with two chiral acetal moieties showed uncontrolled right-handed ( P ) and left-handed ( M ) helical-screw structures.…”
mentioning
confidence: 97%
“…It can be viewed as an Ac 5 c analog in which the γ‐carbon atoms are the junction points to a fused cyclohexene ring. Both ( S,S ) and ( R,R ) isomers were prepared and the conformational properties of the corresponding, terminally protected, homo‐peptides investigated . In the crystal state the ( S,S )‐tripeptide and the ( R,R )‐hexapeptide give rise to the coexistence of right‐handed and left‐handed helical molecules.…”
Section: Side‐chain Chiralitymentioning
confidence: 99%
“…We previously reported that the chiral cyclic dAA (3 S , 4 S )−1‐amino‐(3,4‐dimethoxy)cyclopentanecarboxylic acid [( S , S )‐Ac 5 c dOM ], which only has one side‐chain chiral carbon atom, is able to stabilize short peptide helices and control the helical screw sense of its homopeptides . That is to say, we revealed that the side‐chain chiral centers of cyclic amino acid homochiral homopeptides Cbz‐[( S , S )‐Ac 5 c dOM ] n ‐OMe (Cbz: benzyloxycarbonyl; OMe: methyl ester) can control the helical screw direction into one handedness in solution and also in the crystal state.…”
Section: Introductionmentioning
confidence: 96%